PENCEGAHAN PELECEHAN DAN KEKERASANSEKSUAL PADA ANAK-ANAK DI SDN GEJAYAN - Andhika Giri Persada (UII, 2015)
Sexual harassment any form of behavior that is sexually suggestive takenunilaterally and not expected by people who were subjected to arouse negativereactions such as embarrassment, anger, offended and others to the victims of sexualharassment. Along with the developments of times, also change the minds of nextgeneration, young people today tend to show some parts of their body that invitingpeople to do the sexual harassment.Children do not know what should be done if there is something happen that isharmful to them. Therefore, authors do counseling and distribute posters to preventharassment and sexual abuse of Children especially in SD N Gejayan. The purpose of theextension and distributions of posters are the children know the parts of the body thatshould not be held and be seen by other people who are not well known and did notfollow the strangers and also shouted for help and report if there are people who wantto misbehave to children.